Wdrożenie zrównoważonej karty wyników w firmie FENICE Poland - studium przypadku - Pietrzak, Michał; Prokopowicz, Jerzy (Implementation of balanced scorecard - the case study of FENICE Poland company, 2006)
The paper presents practical issues of BSC implementation based on the case of Fenice Poland. Firstly the company and its business profile are described. Then the implementation of BSC is analyzed step-by-step. Methodology, organization and all phases of the project are described. This description is illustrated by means of graphs and documents generated during the project. Finally the first results of the implementation are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 356-364